2011
DOI: 10.1007/s10571-011-9769-z
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile of THP-1 Monocytes Following Knockdown of DAP12, A Causative Gene for Nasu-Hakola Disease

Abstract: Nasu-Hakola disease (NHD), also designated polycystic lipomembranous osteodysplasia with sclerosing leukoencephalopathy, is a rare autosomal recessive disorder characterized by progressive presenile dementia and formation of multifocal bone cysts, caused by a loss-of-function mutation of DAP12 or TREM2. TREM2 and DAP12 constitute a receptor/adaptor complex expressed on osteoclasts, dendritic cells, macrophages, monocytes, and microglia. At present, the precise molecular mechanisms underlying development of leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The alteration in TYROBP expression under pathological conditions would lead to significant changes in levels of its downstream genes. As demonstrated by a recent study from Satoh et al, in TYROBP knockdown monocytes, a set of 22 genes was identified to be differentially expressed when compared with normal monocytes [27]. More importantly, Zhang and colleagues recently found that overexpression of TYROBP in microglia resulted in dramatic alterations in numerous downstream genes involved in RNA metabolism, cell cycle mitosis, vacuole/autophagy, mitochondrial dysfunction, and histone assembly [7], most of which were closely associated with known molecular pathologies in LOAD including abnormalities of cell cycle as well as dysfunction of autophagy and mitochondrion [47,48].…”
Section: The Expression Of Tyrobp In Ad Brainmentioning
confidence: 91%
See 3 more Smart Citations
“…The alteration in TYROBP expression under pathological conditions would lead to significant changes in levels of its downstream genes. As demonstrated by a recent study from Satoh et al, in TYROBP knockdown monocytes, a set of 22 genes was identified to be differentially expressed when compared with normal monocytes [27]. More importantly, Zhang and colleagues recently found that overexpression of TYROBP in microglia resulted in dramatic alterations in numerous downstream genes involved in RNA metabolism, cell cycle mitosis, vacuole/autophagy, mitochondrial dysfunction, and histone assembly [7], most of which were closely associated with known molecular pathologies in LOAD including abnormalities of cell cycle as well as dysfunction of autophagy and mitochondrion [47,48].…”
Section: The Expression Of Tyrobp In Ad Brainmentioning
confidence: 91%
“…Besides, TYROBP was also reported to suppress inflammation response which involves the repression of cytokine production and secretion [26]. Furthermore, recent findings have suggested that TYROBP-mediated signaling also participated in regulating the expression of multiple genes within the brain [7,27].…”
Section: Tyrobp: Structure Localization and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, Aβ42 peptides were initially solubilized in hexafluoroisopropanol (HFIP; Fluka Chemical, cat# 52512; Sigma-Aldrich, St. Louis MO), aliquoted, and stored at −20°C as an HFIP film. After vacuum evaporation of HFIP, aliquoted peptide was re-suspended with DMSO to 5 mM and diluted to 5 μM into the cell culture media; cells were subsequently stained using a murine amyloid beta MABN10 (red fluorescence λ max ~650 nm; anti-Aβ antibody, clone W0-2; Millipore, Bellerica MA), a TREM-2 antibody (M-227): sc-48765 (green fluorescence; λ max ~510 nm; Santa Cruz, Santa Cruz CA) or DAPI nuclear stain; magnification 60×; note self-aggregation of Aβ42 peptide after 24 h and Aβ42 peptide affinity for TREM2 containing cells (leftmost panels) and internalization (rightmost panel; yellow merge; λ max ~580 nm); additional relevant methods have been described (Griciuc et al, 2013; Zhao and Lukiw, 2013); (B) highly schematicized depiction of the possible actions of an NF-kB-regulated, miRNA-34a-mediated TREM2 sensor-phagocytosis protein down-regulated in AD brain; the triggering receptor for myeloid/microglial cells (TREM2) is a variably glycosylated transmembrane receptor known to be enriched in the microglial cell plasma membrane; signaling via the tyrosine kinase-binding protein (DNAX activation protein 12) [TYROBP (DAP12)] accessory receptor results in phagocytosis and ultimately, clearance of Aβ42 peptides (red ovals) from the extracellular space (Satoh et al, 2011; Benitez et al, 2013; Forabosco et al, 2013; Hickman and Khoury, 2014); interestingly, TREM2 knockout/knockdown mice have attenuated immunological and inflammatory responses and/or increases in age-related neuroinflammatory markers and cognitive deficiency (Jiang et al, 2013; Sieber et al, 2013); TYROBP knockout mice exhibit immune system deficits and an impairment in microglial cell differentiation (Nataf et al, 2005; Sieber et al, 2013); it is not clear what, if any, contribution TREM2 makes directly to phagocytosis and Aβ42 clearance (question mark) without TYROBP (DAP12); while no deficits in TYROBP (DAP12) have been observed in sporadic AD brain, insufficient TREM2 may be in part responsible for the inability to adequately phagocytose Aβ42 peptides, resulting in their buildup and self-aggregation in the extracellular space. Inset: miRNA-34a is found to be significantly increased in AD hippocampal CA1 and superior temporal lobe and in stressed microglial cells; miRNA-34a targeting of the TREM2 mRNA 3′-UTR appears to be in part responsible for this (see text); because miRNA-34a is encoded on an NF-kB-sensitive transcript, both anti-NF-kB and/or anti-miRNA strategies may be clinically useful in the restoration of homeostatic phagocytosis in the brain and CNS.…”
mentioning
confidence: 99%